Characteristic of pineapple leaf fibre using different methods at minimum level with the assist of mechanical breaker - Sukri, N.A.; Saiman, M.P.; Ishak, K.; Wahab, Md Saidin; Rashad, N.F.A. (UTEM, 2020)
Pineapple cultivation has resulted in wastage of pineapple leaf fibre (PALF) where it can be used as renewable natural resources. PALF is able to be used in various textile and non-textile products. However, to gain fibre as raw material requires suitable processing methods. Several methods were used in this experiment to identify suitable process using minimal resources. There were four methods used to produce open PALF which are unchanged extracted PALF, unchanged extracted PALF and going through PALF breaker, extracted PALF going water retting for 4 days and extracted PALF treated with 1% NaOH and going through PALF breaker. All PALFs were opened using Shirley Trash Analyser, and analysed by looking at its trash and microscopy. The results found that the assist of water retting and NaOH treatment and going through PALF breaker give better results for textile and non-textile application.